2020
DOI: 10.1097/jcma.0000000000000414
|View full text |Cite
|
Sign up to set email alerts
|

Preventing epilepsy after traumatic brain injury: A propensity score analysis

Abstract: Background: Due to the potential consequences of post-traumatic epilepsy (PTE) exacerbating secondary injury following traumatic brain injury (TBI), the use of antiepileptic drugs (AEDs) is an accepted option for seizure prophylaxis. However, there is only a paucity of data that can be found regarding outcomes surrounding the use of AEDs. The purpose of this retrospective study is to evaluate whether the prophylactic administration of AEDs significantly decreased the incidence of PTE, when consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 31 publications
0
21
1
Order By: Relevance
“…One-half of the studies reported patients with mild and moderate TBI separately . Most studies, except for 2, had significantly more (>80%) mild TBI than moderate (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One-half of the studies reported patients with mild and moderate TBI separately . Most studies, except for 2, had significantly more (>80%) mild TBI than moderate (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, all the studies were graded as good quality on the NOS (Table 2). Common reasons for decreased quality were only including patients at rehabilitation hospitals and failure to provide adequate follow-up information or descriptions of patients lost to follow-up …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the different mechanisms of the different ASMs and the limitation of the available evidence, the use of ASMs for the prevention of epileptic seizures after TBI is still controversial. A propensity score analysis conducted by Liou et al ( Liou et al, 2020 ). Revealed that ASMs were ineffective in preventing seizures after TBI, and the benefit of routine prophylactic ASMs treatment in TBI patients needs to be reassessed ( Saletti et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the location and severity of the bleeding, PTE can occur immediately within 24 h after trauma, early within the first 7 days following trauma, and late after 7 days following trauma ( Turnbull et al, 2016 ; Chartrain et al, 2017 ). Over the past 30 years, the cumulative incidence of PTE was 2% for mild brain injury, 4% for moderate brain injury, and 15% for severe brain injury ( Saletti et al, 2019 ; Liou et al, 2020 ). PTE following TBI may further exacerbate the effects of TBI on memory and cognition, damage the cerebrovascular system or blood-brain barrier, and lead to depression or post-traumatic stress disorder ( Castriotta et al, 2007 ; Luo et al, 2014 ; Muccigrosso et al, 2016 ; Vos et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%